A Field Study Of Management And Husbandry Factors Affecting Reproductive Performance Of Dairy Cows In Malacca Malaysia - Manefield, Geoffrey W (1985)
The problem of poor reproductive per formance and lack of profit from small holders ' dairy cows in Halacca was addressed during the period July 1981 to May 1983 . Performance of 290 cows on 82 farms with varying feeding and management regimes were studied over a period of at least one year. Performance history and physical examination of the cows at repetitive visits provided data which was analysed for significant differences (P < 0. 05) in productive and reproductive performance against variations in husbandry , and population character is tics of cows and farmers. Increasing parity from one to three or greater decreased calving to conception interval mean by 4 . 2, median by 5.5 and for 90% of cows pregnant by 5.6 months at a level of feeding 0.5 NRC recommendations . With full feeding the corresponding figures were 1.8,1.7 and 2.1 ( but between parity one and two 2.7,3.0 and 4.9) . Parity exerted its great est effect between parity one and two . No increase in ( milk ) production peak occurred with increase in parity.